EFFECT OF BUBBLE-BLOWING BREATHING THERAPY ON OXYGENATION IN BRONCHOPNEUMONIA: A QUASI-EXPERIMENT STUDY - Novita Setianingsih; Nafisatun Nisa; Siti Lestari; Sri Hartini M. A. (Universitas Airlangga, 2026)
Introduction: Bronchopneumonia is a common cause of lower respiratory infections in children and often leads to impaired oxygenation and breathing difficulties. There is an urgent need for non-invasive, child-friendly interventions to support respiratory recovery in hospitalized children. This study aimed to evaluate the effectiveness of a modified breathing intervention, specifically bubble-blowing therapy, on oxygenation outcomes in children with bronchopneumonia. Methods: A quasi-experimental one-group pretest–posttest design was employed, involving 31 children diagnosed with bronchopneumonia, selected through purposive sampling at SMC Telogorejo Hospital. The intervention consisted of a 10-minute session of modified pursed-lips breathing combined with bubble blowing. Oxygenation was assessed by measuring respiratory rate (RR), heart rate (HR), and oxygen saturation (SpO₂) before and after the intervention. Paired t-tests were used for statistical analysis, with significance set at p ≤ 0.05. Results: Post-intervention findings showed significant improvements: the mean RR decreased from 28.7 to 24.13 breaths/min, HR decreased from 122.87 to 112.90 beats/min, and SpO₂ increased from 95.16% to 99.23% (all p = 0.000). Conclusions: Bubble-blowing breathing therapy, a playful adaptation of pursed-lips breathing, significantly improved respiratory rate, heart rate, and oxygen saturation in children with bronchopneumonia. These findings suggest that this approach may serve as a simple and engaging method to enhance short-term oxygenation in pediatric care. Further studies incorporating control groups and longer follow-up periods are needed to confirm these findings and explore long-term effects.